AGE HARDENING BEHAVIOR OF A HYPO-STOICHIOMETRIC FE3AL INTERMETALLIC COMPOUND - PARK, JW; MOON, IG (ELSEVIER SCIENCE SA, 1992)
Kinetics of age hardening and microstructural changes were studied to clarify the principal factor responsible for the hardening behavior of a hypo-stoichiometric Fe3Al alloy initially D0(3) ordered at 400-degrees-C. The alloy revealed two-stage hardening behavior in a lower temperature region of two-phase fields and one-stage hardening curves in an upper region. The first stage hardening occurred very rapidly and was independent of aging temperature. An incubation time was required for the second stage hardening, retarding with decreasing temperature. The early stage hardening was related to the decrease in the degree of order and the second stage hardening was caused by the precipitation of the a phase.
Keywords: FE-AL ALLOYS; IRON-ALUMINUM ALLOYS; ORDER